Dynamics characterization of modified Gross-Pitaevskii equation - Filho, Victo S.; Machado, Birajara S. [UNESP]; Francisco, Gerson; Tomio, Lauro [UNESP] (Elsevier, 2013)
The dynamics of dissipative and coherent N-body systems, such as a Bose-Einstein condensate, which can be described by an extended Gross-Pitaevskii formalism, is investigated. In order to analyze chaotic and unstable regimes, two approaches are considered: a metric one, based on calculations of Lyapunov exponents, and an algorithmic one, based on the Lempel-Ziv criterion. The consistency of both approaches is established, with the Lempel-Ziv algorithmic found as an efficient complementary approach to the metric one for the fast characterization of dynamical behaviors obtained from finite sequences. © 2013 Elsevier B.V. All rights reserved.
Keywords: Bose-Einstein condensates; Chaos; Nonlinear dynamics; Numerical simulations; Time series analysis; Dynamical behaviors; Finite sequence; Gross-Pitaevskii equation; Lyapunov exponent; N-body system; Two Approaches; Algorithms; Chaos theory; Computer simulation; Dynamics; Lyapunov methods; Statistical mechanics; Bose-Einstein condensation